An Appropriate Method of Calculating Return for the Pharmaceutical Companies Enlisted under FTSE all-share index - Mohammad Rabiul, Hossain (2006)
Over the last several decades, a substantial body of research has been done to determine the most suitable method of calculating shareholders rate of return. Rate of return is a fundamental concept in any kind of investment decision. There are several useful methods to calculate the shareholders rate of return, namely the Capital Asset Pricing Model, Discounted Cash Flow Model, Arbitrage Pricing Theory and Three factor Model. Each of these models has its own advantages and disadvantages, proponents and opponents. Which method to use depends on the assumptions made, industry practice and also on the evidence from the established literature.